Memories in the Service of the Hindu Nation: the Artlife of the Partition of India - Kohli, Pranav (New Delhi Cambridge University Press, 2023)
this book is based on 14 months of ethnographic fieldwork in Delhi and its surroundings between 2017 and 2018 with Partition survivors from West Punjab and the North-West Frontier Province. It focusing on Hindu Nationalism in India.
Keywords: Kohli, Pranav; Partition of India; Hindu Nation; Partition of India; Hindu Nation